Pelatihan Dan Pendampingan Cara Kreatif Melaksanakan Pembelajaran Matematika Secara Online Bagi Guru-Guru Sekolah Dasar GMIT OEPURA - Juliana M. H. Nenohai; Ch K. Ekowati; Ofirenty Elyada Nubatonis; Magdalena Wangge; Aleksius Madu (Jurnal Nasional Pengabdian Masyarakat, 2022)
The Community Partnership Program at SD GMIT Oepura was motivated by problems experienced by partners in terms of limited integration of technology in learning due to the low ability of teachers to master technologies that support learning. Therefore, the FKIP Undana Mathematics Education PKM team conducted training and assisted participants to a) make learning videos using the bandicam application, b) use the wordwall application to carry out learning evaluations and c) carry out the learning process online in creative ways. The outputs of this activity were a) participants were able to design learning videos using the Bandicam application, b) participants were able to design evaluations and carry out learning evaluations by utilizing Wordwall and c) participants were able to carry out online learning using complete learning videos.